2019
DOI: 10.3390/jcm8091456
|View full text |Cite
|
Sign up to set email alerts
|

Uncharted Waters: Treating Trauma Symptoms in the Context of Early Psychosis

Abstract: Psychosis is conceptualized in a neurodevelopmental vulnerability-stress framework, and childhood trauma is one environmental factor that can lead to psychotic symptoms and the development of psychotic disorders. Higher rates of trauma are associated with higher psychosis risk and greater symptom frequency and severity, resulting in increased hospitalization rates and demand on outpatient primary care and mental health services. Despite an estimated 70% of individuals in the early stages of psychosis reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…A further challenge in implementing therapy to address trauma in psychosis is whether, and how, to integrate tf-CBT and CBTp for people who have both re-experiencing and psychosis. Consecutive delivery of targeted therapies is a possibility and has been researched in a US context ( 9 , 30 ). However, it may not be optimally acceptable nor effective to treat PTSD and psychosis separately.…”
Section: Introductionmentioning
confidence: 99%
“…A further challenge in implementing therapy to address trauma in psychosis is whether, and how, to integrate tf-CBT and CBTp for people who have both re-experiencing and psychosis. Consecutive delivery of targeted therapies is a possibility and has been researched in a US context ( 9 , 30 ). However, it may not be optimally acceptable nor effective to treat PTSD and psychosis separately.…”
Section: Introductionmentioning
confidence: 99%
“…In consequence, there is an urgent need for studies to analyse the treatment of PTSD in persons diagnosed with psychotic disorders, and to determine the usefulness of interventions addressing symptomatic, psychotic and post-traumatic stress modalities. In this respect, Folk et al (2019) suggested an approach to treating PTSD symptoms in the context of early psychosis care. These authors suggested that individuals with comorbid psychoses and posttraumatic stress symptoms can be appropriately and safely treated with 'Trauma-Integrated Cognitive Behavioural Therapy for Psychosis' (Folk et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, Folk et al (2019) suggested an approach to treating PTSD symptoms in the context of early psychosis care. These authors suggested that individuals with comorbid psychoses and posttraumatic stress symptoms can be appropriately and safely treated with 'Trauma-Integrated Cognitive Behavioural Therapy for Psychosis' (Folk et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive Behavioural Therapy for Psychosis (CBTp) has historically demonstrated variable and at times limited effect sizes in producing a range of outcomes in psychosis (Jones et al, 2018; Laws et al, 2018; Mehl et al, 2015). Recent trends in CBTp research have focussed on symptom‐specific approaches to identifying and addressing maintenance factors, such as addressing the role of worry processes and sleep in delusional beliefs (Freeman et al, 2015; Lincoln & Peters, 2019), the role of trauma in both hallucinations and delusions (Folk et al, 2019; Larkin & Read, 2008) and the role of attachment in voice hearing and paranoia (Berry et al, 2008; Gumley et al, 2014). A recent meta‐analysis reported improvements in CBTp for addressing delusions over time, suggesting that the shift towards symptom‐focussed CBTp approaches offers improved focus and efficacy in addressing specific difficulties compared to broader packages (Sitko et al, 2020).…”
Section: Introductionmentioning
confidence: 99%